ANALISIS REAKSI PASAR MODAL INDONESIA TERHADAP PERISTIWA NON EKONOMI (STUDI KASUS PERISTIWA BOM JW MARIOTT / RITZ CARLTON 17 JULI 2009) - M. Taufik Hidayat (MEDIA, 2012)
Capital market is one of the economic instrument with rapid developments. It is become an indicator and supporting economic development of a country. Capital market gives reaction to any event which contents with information, economic event as well as non economic event. Safety situation in the Country have a close relationship with stability and the economic performance of a country. In Indonesia, safety situation seem can’t be separated from capital market reaction. This research attempt to analyze capital market reaction to safety situation in the country, in this case is Bombing event on JW Mariott / Ritz Carlton Hotel at17th July 2009. Capital market reaction measured by the abnormal return, trading volume activity and security return variability. The examination of market reaction used event study analysis technique and the samples selected by purposive random sampling method from LQ 45 in BEI (Indonesia Security Exchange) during the observation periode. The calculation of abnormal return based from expected return which is exceeded from linear regression technique. The result showed that Bombing event on JW Mariott / Ritz Carlton hotel as a unsafety situation had an impact on Indonesia capital market. There were a reaction of positive abnormal return on the day after the bombing event but in the few days after, market had back to a normal situation. The statistical test result that there are no significant differences among abnormal return, trading volume activity and security return variability around the event of JW Mariott / Ritz Carlton bombing.